Konfigurasi Serpentine-Paralel dan Paralel-Serpentine pada Pipa Fluida Pemanas Air Surya Sistem Thermosiphon - Hatib, Rustan (Jurnal Rekayasa Mesin, 2015)
The aim of this research is to compare the performance of two differences tube configuration in solar hot water collector thermosiphon system of Serpentine-Parallel and Parallel-Serpentine. Not only the tubes configuration are not the same, but also the collector materials, such as hot water reservoir and heat absorber are differences. For example, fiberglass and stainless steel reservoirs are compared in terms of long-lasting heat isolation. Likewise, copper tubes configuration between serpentine-parallel and parallel-serpentine are shown in association with mass flow rates and times consume to heat the water within the tubes. The test results show that parallel-serpentine configuration has higher performance (around 50%) than that of serpentine-parallel (approximately 35%). It is possibly because of fluid velocity within the tube configuration.